Xenon Does Not Increase Heart Rate–corrected Cardiac QT Interval in Volunteers and in Patients Free of Cardiovascular Disease. (September 2015) - Neukirchen, Martin; Schaefer, Maximilian S.; Kern, Carolin; Brett, Sarah; Werdehausen, Robert; Rellecke, Philipp; Reyle-Hahn, Matthias; Kienbaum, Peter
Abstract : Background: Impaired cardiac repolarization, indicated by prolonged QT interval, may cause critical ventricular arrhythmias. Many anesthetics increase the QT interval by blockade of rapidly acting potassium rectifier channels. Although xenon does not affect these channels in isolated cardiomyocytes, the authors hypothesized that xenon increases the QT interval by direct and/or indirect sympathomimetic effects. Thus, the authors tested the hypothesis that xenon alters the heart rate–corrected cardiac QT (QTc) interval in anesthetic concentrations. Methods: The effect of xenon on the QTc interval was evaluated in eight healthy volunteers and in 35 patients undergoing abdominal or trauma surgery. The QTc interval was recorded on subjects in awake state, after their denitrogenation, and during xenon monoanesthesia (Fet Xe > 0.65). In patients, the QTc interval was recorded while awake, after anesthesia induction with propofol and remifentanil, and during steady state of xenon/remifentanil anesthesia (Fet Xe > 0.65). The QTc interval was determined from three consecutive cardiac intervals on electrocardiogram printouts in a blinded manner and corrected with Bazett formula. Results: In healthy volunteers, xenon did not alter the QTc interval (mean difference: +0.11 ms [95% CI, −22.4 to 22.7]). In patients, after anesthesia induction with propofol/remifentanil, no alteration of QTc interval was noted. After propofol was replaced with xenon, the QTc interval remained unaffected (417 ± 32 ms vs. awake: 414 ± 25 ms) with a mean difference of 4.4 ms (95% CI, −4.6 to 13.5). Conclusion: Xenon monoanesthesia in healthy volunteers and xenon/remifentanil anesthesia in patients without clinically relevant cardiovascular disease do not increase QTc interval. Abstract : No prolongation of heart rate–corrected cardiac QT intervals was observed in volunteers during xenon monoanesthesia or in patients without preexisting long QT syndrome during xenon-based anesthesia.